Efficient synthesis of 2-amino-3-methylenephthalimides by a palladium-catalyzed intramolecular aminocarbonylation. Issue 12 (17th June 2020) - Pan, Guoshuai; Yuan, Yumeng; Su, Lv; Zhang, Xiaofeng; Huang, Qiufeng
Abstract: An efficient synthesis of 2-amino-3-methylenephthalimide through palladium-catalyzed intramolecular aminocarbonylation has been developed. The reaction carried out under atmospheric pressure of CO and provided diversified 2-amino-3-methylenephthalimides in reasonable to good yields from o-iodoacetophenone phenylhydrazone, which are readily derived from phenylhydrazines and 2-iodoacetophenones. Graphical Abstract: UF0001